Analysis of I'jāz Balāghi in Surah Yāsīn: A Comparison of Tafsir Al-Kasysyāf and Ṣafwah At-Tafāsir - Rosmila Rosmila; Ade Naelul Huda; Ahmad Syukron (Jurnal El-Thawalib, 2026)
This study aims to analyze the concept of I’jāz Balāghī in Surah Yāsīn through a comparative study of Tafsīr al-Kasysyāf by al-Zamakhsharī and Ṣafwah al-Tafāsīr by ‘Alī al-Ṣābūnī. The study of Qur’anic inimitability, particularly in its linguistic dimension, has become increasingly significant amid contemporary academic debates that question the authenticity of the Qur’an, thus requiring a balāghah-based approach as evidence of its rhetorical superiority. This research employs a qualitative library research method with a descriptive-analytical approach and a comparative method. The data sources consist of primary data from Tafsīr al-Kasysyāf and Ṣafwah al-Tafāsīr, as well as secondary data from literature on ‘ulūm al-Qur’ān, balāghah, and relevant academic journals. Data were collected through documentation by identifying and classifying verses of Surah Yāsīn containing elements of ma‘ānī, bayān, and badī‘. The data analysis was conducted by describing each mufassir’s interpretation and comparing their similarities, differences, and methodological strengths in explaining I’jāz Balāghī. The findings reveal that I’jāz Balāghī in Surah Yāsīn is manifested through the integration of ma‘ānī, bayān, and badī‘, forming both rhetorical and argumentative structures. Tafsīr al-Kasysyāf emphasizes a deep linguistic-analytical approach, while Ṣafwah al-Tafāsīr offers a more systematic and applicative explanation. Comparatively, both exegeses complement each other in understanding the multidimensional nature of I’jāz Balāghī, thereby reinforcing the argument of the Qur’an’s inimitability from a linguistic perspective.